Growth and assessment of InGaN quantum dots in a microcavity: A blue single photon source - Oliver, R; Jarjour, A; Taylor, R; Tahraoui, A; Zhang, Y; Kappers, M; Humphreys, C (2008)
Using a modified droplet epitaxy approach in metal-organic vapour phase epitaxy (MOVPE), we have grown InGaN quantum dots (QDs) on top of a 20-period AlN/GaN distributed Bragg reflector (DBR). The QDs were located at the centre ofa ca. 182 nm GaN layer. To complete the cavity a three-period SiOx/SiNx DBR was deposited onto the GaN surface. Despite the evolution of roughness during the growth of the AlN/GaN DBR. due to cracking of the AlN layers, a cavity mode was observed, with a quality-factor of similar to 50. Enhanced single QD emission was observed in micro-photoluminescence studies of the sample, and photon-correlation spectra provided evidence for single photon emission. (C) 2007 Elsevier B.V. All rights reserved.